Corporate Social Responsibility in Global Supply Chains: Deeds Not Words - Holger Görg; Aoife Hanley; Adnan Seric (Sustainability, 2018)
The disconnect between the lofty aspirations of firms claiming Corporate Social Responsibility (CSR) and their shortcomings in practice have caused some observers to question its usefulness. The fallout from events like the Rana Plaza catastrophe has highlighted some of these shortcomings—namely, deficiencies in how multinational enterprises (MNEs) transact with suppliers in developing countries. Specifically, our paper aims to investigate whether or not MNEs behave hypocritically by examining the alignment of CSR to business practices in MNE affiliates in developing countries. To answer this question, we apply standard ordinary least squares (OLS) techniques to data for over 1000 MNEs that claim to have a CSR ethos. We find that CSR-active enterprises report significantly higher worker wages, ceteris paribus. Local African suppliers benefit from CSR through knowledge transfer, but only when MNEs make tangible investments in supplier development.
Keywords: F23; M14; O14; 330; corporate social responsibility; corporate hypocrisy; Africa; wages; knowledge transfer